ChemInform Abstract: A Survey of Advancements in Nucleic Acid‐Based Logic Gates and Computing for Applications in Biotechnology and Biomedicine. Issue 17 (April 2015) - Wu, Cuichen; Wan, Shuo; Hou, Weijia; Zhang, Liqin; Xu, Jiehua; Cui, Cheng; Wang, Yanyue; Hu, Jun; Tan, Weihong
Abstract Review: 100 refs.